Análise das mudanças no uso do solo nos distritos de Cruzeiro dos Peixotos e Martinésia em Uberlândia (MG) entre 1997 e 2017 - (:unkn) unknown (Universidade Federal de Goiás, 2018)
In Brazil, since the beginning of its colonization, the degradation of the Brazilian biomes was present. At the beginning of the eighteenth century this occupation reaches the lands where currently the city of Uberlândia (MG) is located, along with it, also comes the process of degradation that extends to the present day. It is in this context, of occupation of the Cerrado, that the Districts studied, Cruzeiro dos Peixotos and Martinésia, located in the northern portion of the municipality of Uberlândia (MG), are inserted. The main objective of this work was to analyze the changes in land use, in the referred Districts, between 1997 and 2017, from a socioenvironmental perspective. In the development of this one, a study was carried out to detect what was altered in the natural area, by means of overlapping, and comparison of cartographic data and remote sensing, obtained with the aid of satellite images, considering the cuts of the years of 1997, 2007 and 2017. The research area, although in a differentiated way, went through processes of urbanization and industrialization (inputs and agricultural equipment) and consequently modernization of agriculture, changes in the technological, social, economic and mainly environmental fields. The importance of knowing the real potentialities and limitations of use and occupation of a given area, through registries and monitoring, allow the evaluation of future potentialities and impacts. The area studied was delimited from the production of a base map which was created using images from the Google Earth program. These images were transferred to digital format using ArcGIS and SPRING. The next step was the acquisition of TM and OLI images LANDSAT 5 and 8, scale 1: 100,000, bands 3B, 4G and 5R, orbit / point 221/073 of the years 1997, 2007 and 2017 achieved in DPI / INPE - 2017. The bands 3B, 4G and 5R (sensor TM) and 3B, 5G and 7R (OLI sensor), orbit / point 221/073 from the years of 1997, 2007 and 2017 were selected for a better view of the relief, drainage and soil cover in the study area. To enable interpretation, it was necessary to group some land use classes: Water, Forest Formation, Cerrado, Pastures, Annual Culture, Forestry and Exposed / Burned Soils. In the area under study for the artificial lakes of the Hydroelectric Power Plants they are small hydroelectric power plants or it has not increased a new type of enterprise in the region that are the allotments of rural areas for recreational farms. The modernization of agriculture was not restricted to new crops, reaching small landowners, and expropriating those who did not fit the new model. In the Districts surveyed, what is perceived is that farmers who have not been able to keep up with the modernization of agriculture rent their land for cultivation or pasture, with small parcels of land near their headquarters being used for their use.
Analysis of changes in the use of soil in the districts of Cruzeiro of the Peixotos and Martinésia between Uberlândia (MG)
Keywords: Uso do solo; Mudanças; Imagem; Martinésia; Cruzeiro dos Peixotos; Use of the soil; Changes; Image; Martinésia; Cruzeiro dos Peixotos; CIENCIAS HUMANAS::GEOGRAFIA